2017
DOI: 10.1038/tp.2017.82
|View full text |Cite
|
Sign up to set email alerts
|

Exercise alters mouse sperm small noncoding RNAs and induces a transgenerational modification of male offspring conditioned fear and anxiety

Abstract: There is growing evidence that the preconceptual lifestyle and other environmental exposures of a father can significantly alter the physiological and behavioral phenotypes of their children. We and others have shown that paternal preconception stress, regardless of whether the stress was experienced during early-life or adulthood, results in offspring with altered anxiety and depression-related behaviors, attributed to hypothalamic–pituitary–adrenal axis dysregulation. The transgenerational response to patern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 91 publications
5
107
2
Order By: Relevance
“…The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 . In animal studies, paternal exposures to high-fat and high-sugar diets produce metabolic disturbances in offspring 54 , and both stress and exercise affect stress responses of the offspring [55][56][57] . Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…The paternal preconception environment modulates the RNA content of the developing sperm, with possible effects on post-fertilization development and offspring phenotypes 53 . In animal studies, paternal exposures to high-fat and high-sugar diets produce metabolic disturbances in offspring 54 , and both stress and exercise affect stress responses of the offspring [55][56][57] . Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Importantly, the authors observed that exercise increased DNA methylation at promoters of several genes associated with brain pathologies such as schizophrenia and Parkinson disease (Denham et al, 2015). Recently, it has been reported that physical exercise alters the expression of miRNAs in paternal sperm, whereas suppresses the reinstatement of fear memory and reduces anxiety in male mice offspring (Short et al, 2017). …”
Section: Can the Beneficial Effects Of Physical Exercise Be Transmmentioning
confidence: 99%
“…Third, more direct causal proof still needs to be provided and 'reversal' studies showing a correction of epigenetic alterations like in Gapp et al [36 ] or in Benito et al [34 ] are needed. Reversal studies could employ parental and/or offspring environmental manipulations known to have transgenerational effects such as EE [9,34 ,36 ] or exercise [48], or molecular manipulations in germ cells such as ncRNA silencing [34 ] or epigenome editing through CRISPR-dCas [49]. Importantly, different mechanisms may be responsible for the transmission of phenotypes depending on the environmental stimuli, the time window and severity of exposure, and the time of analyses (whether shortly or long after exposure).…”
Section: Discussionmentioning
confidence: 99%